Computational analysis of large recessed silicon carbide grinding wheels. (11th May 2010) - Jackson, Mark J.
The analysis of large recessed silicon carbide grinding wheels made with recessed features and a vitrified spinning at different rotational speeds is presented. Using a computational approach, it was possible to determine maximum principal stresses in the wheel together with the location of those stresses. The geometry of vitrified wheels considered included a plain-sided rotating wheel and a recessed large cup grinding wheel. Calculations were conducted to determine maximum stress in parallel-sided and recessed cup wheels. Relevant factors of safety and bursting speed were also calculated and compared with experimental data generated with a manufacturer of such wheels. The paper shows the applicability of a method developed for taking account of stress concentrations at the recesses of large cup-shaped silicon carbide grinding wheels bonded with a vitreous bonding system.